Development of interaction management tools in B2B markets - M. V. Orlova; V. V. Orlov (Вестник университета)
The article is devoted to the problem of improving interaction in B2B markets. By analyzing the literature on the issues under study, the authors have identified a trend in the customer management development in B2B markets towards a unique experience creation along the entire path of interaction between an account and a company. This is a business marketing strategy aimed at understanding, engaging and providing customized services and content to target accounts. The strategy involves using marketing techniques to engage the entire organization by targeting multiple stakeholders within a single potential account. The use of CJM as a methodology currently used in B2C markets has been justified and recommendations for its application in B2B made. CJM allows companies to align their business processes and resources with the needs of accounts, ensuring smooth teamwork. Engagement tools used in account engagement management have been systematized, helping to effectively shape the account experience; engagement performance metrics have been identified. The engagement tools implementation provides the cross-functional integration needed to engage with larger accounts, aligning marketing with sales and service. The article focuses on personalizing engagement with decision makers. The research analysis also revealed the features and trends of content customization within the ABM programs.